Research and design of data warehouse in coal mine enterprise - Sun Gang; Zhang Ruixin; Zhou Huaping; Pan Qidong; Yan Shaoling (2010 2nd IEEE International Conference on Information Management and Engineering, 2010)
The paper introduce the necessity and urgency of building data warehouse in coal mine enterprise, and then research the characteristics and architecture of data warehouse in coal mine enterprise; according to the inherent characteristics of coal mine enterprise, the typical subjects of data warehouse in coal mine enterprise are built; and according to system requirements of data warehouse in coal mine enterprise, star schema is adopted in data warehouse in coal mine enterprise; Anally, research the applications of OLAP technology and data mining technology in data warehouse in coal mine enterprise.